can someone explain to me this please....
What is the difference between
ax^2+bx+c and ax^2+bx+c=0
One is an expression and the other is an equation. (An equation uses an equals sign.)
I hope this helps and is what you were asking.
well you got to equal it e.g:
3x-1=5
3x=5+1( for removing the "-1" you got to add 1 so you gotta do the same on the other side )
3x/3= 5/3( to remove the 3 from 3x as 3x= 3X x so you got to do the same both the side to keep it equal
1x=2
x=2
hope that the answer to your question!!